Electron exchange reactions between tungsten hexachloride and nitrogen donors - Bortoluzzi, Marco; Foschi, Francesco; Marchetti, Fabio; Pampaloni, Guido; Zacchini, Stefano (Polyhedron, 2016)
The 1:1 molar reactions of WCl6 with a selection of aliphatic amines, in CH2Cl2 at room temperature, led to the isolation of the W(V) salts [amineH][WCl6] (amine=NEt3, 1; NHEt2, 2; pyrrolidine, 3; NH2CH2Ph, 4), in 47-57% yields. Analogously, [dmpH][WCl6], 5, was obtained in 55% yield from WCl6/3,5-dimethylpyrazole (dmp). The 1:2 molar reactions of WCl6 with NEt3 and NH2CH2Ph afforded the W(IV) salts [NHEt3]2[WCl6], 6, and [NH3CH2Ph]2[WCl6], 7, in 50-52% yields, respectively. Compounds 1-7 were characterized by analytical and spectroscopic methods, in addition the molecular structures of 2, 5 and 6 were ascertained by single crystal X-ray diffraction studies. A possible pathway regarding the 1:1 molar reaction of WCl6 with triethylamine is proposed on the basis of DFT calculations. The iminium [PhCH=NH2]+ cation was identified as a co-product in the mixtures obtained from WCl6 and variable amounts of benzylamine.
Gesehen am 14.05.2020